Levels of acceptability of Biogas Technology among livestock raisers in the 3rd District of Iloilo - Prosianos, Percy Basil M.
The study was made to measure the acceptability levels of biogas technology among the livestock raisers in the Third District of Iloilo. Biogas technology was introduced by the Department of Agriculture in Iloilo in the mid-90s with the aim of controlling pollution brought about by livestock raising as well as harnessing the non-conventional energy - methane gas emitted by decaying livestock manure for cooking and lighting. The study aimed to economically quantify and qualify the benefits derived from the use of biogas technology and relates it to its acceptability. Likewise, the study sought to assess the impact of biogas use on the farmers' lives and environment. The Third District of Iloilo, composed of nine towns, was chosen as the study area because among the six districts of Iloilo, it contributed the most to the whole livestock population of Iloilo (102, 180 head, as of March 2003). The respondents in this study were randomly chosen at seven farmers per town distribution, The employment of interviews to gather primary data was done while secondary data was gathered from related materials and from reports of government and non-government technicians. Analysis of data gathered was done through simple descriptive methods like frequency distribution. The study reveals that biogas technology is quite popular among livestock raisers in Iloilo, particularly in the Third District, but only quite a few of them have actually ado[ted it (0.0001%). Among those who adopted it, only a few (0.00005%) continue to use it because of certain problems elated to puncturing of the plastic material used. The vast majority who stopped using this technology were constrained by the high costs and the question of durability of material used.